Diseased Estate: historiographic grotesque - Costantino, Thea (Curtin University, 2010)
This thesis proposes the historiographic grotesque as an interdisciplinary aesthetic and thematic mode which occurs in representations of the past. Characterised by the contradictory interplay of horror and pleasure, the grotesque provides the grounds for an affective engagement with history. The historiographic grotesque thus operates in opposition to those modes of history which stress the importance of objectivity in representations of the past, assert the authority of the historian and promote the possibility of understanding the past as it was really lived. In undermining this approach, the historiographic grotesque can contribute to a critique of history while offering alternative ways of interpreting the past.The written component of this thesis examines incursions of the grotesque in a range of theoretical and creative works which address historical transition and rupture, critique official modes of history, and depict the past as a site of death and uncanny return.The creative component of this thesis is a suite of two-and three-dimensional works with accompanying text which presents a grotesque historical narrative of colonial Western Australia, referencing the materials of wax and photography to present an uneasy and unreliable account of the past. Rather than illustrating the written component of the thesis, the creative research offers a parallel investigation of the significance of the grotesque for considerations of history.